2019
DOI: 10.1038/s41574-019-0280-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of growth hormone on adipose tissue: old observations, new mechanisms

Abstract: The ability of growth hormone (GH) to induce adipose tissue lipolysis has been known for over five decades; however, the molecular mechanisms that mediate this effect, as well as the ability of GH to inhibit insulin-stimulated glucose uptake, have been scarcely documented. In this same timeframe, our understanding of adipose tissue has evolved to reveal a complex structure with distinct types of adipocytes, depot-specific differences, a biologically significant extracellular matrix and important endocrine prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 160 publications
(183 reference statements)
1
90
0
Order By: Relevance
“…The changes in AT mass we observed with GHR antagonist therapy are consistent with reversal of the mechanisms by which GH reduces AT, in particular VAT, mass [ 36-41 ]. The effects of pegvisomant on fat metabolism have been studied in a few prior, short-term studies in acromegaly and healthy subjects and showed no changes [ 31 , 42 , 43 ] or suppression of lipid mobilization and oxidation [ 44 ].…”
Section: Discussionsupporting
confidence: 67%
“…The changes in AT mass we observed with GHR antagonist therapy are consistent with reversal of the mechanisms by which GH reduces AT, in particular VAT, mass [ 36-41 ]. The effects of pegvisomant on fat metabolism have been studied in a few prior, short-term studies in acromegaly and healthy subjects and showed no changes [ 31 , 42 , 43 ] or suppression of lipid mobilization and oxidation [ 44 ].…”
Section: Discussionsupporting
confidence: 67%
“…The recuperation of the GH–IGF-1 axis after body weight normalization suggests an acquired and reversible disturbance; however, the reduced GH secretion in obesity may favor the retention of adipose tissue, and contribute to perpetuation of the obese state. GH’s most characteristic metabolic action is to induce adipose tissue lipolysis [ 49 ]. GH directly stimulates adipose tissue lipolysis in a GH receptor-dependent manner [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…GH is widely recognized for its anabolic and lipolytic functions, stimulating muscle and bone growth mediated by IGF1 secretion. In adipocytes, stimulated GH receptors induce lipolysis through oxidation and triacylglycerol breakdown [86]. On the other hand, the homeobox transcript antisense intergenic RNA (HOTAIR) is part of the long noncoding RNAs class that is suggested to regulate the expression of numerous signalling transcripts and is a potential biomarker for several types of cancer [87].…”
Section: Functional Analysismentioning
confidence: 99%